Locana-vimarśaḥ - Jhā, Vaidyanātha (Mithilā Vidyāpīṭha granthamālā. Navīnagranthāvalau, 1978)
Study on Rājānaka Abhinavagupta's Dhanyālokalocana, 11th century commentary on Dhanyāloka of Ānandavardhana, 9th century exponent of the Dhvani school of Sanskrit poetics.